Self-Management in Anxiety and Depression: A Psychometric Evaluation of a Questionnaire - Krijnen-de Bruin, Esther; Draisma, Stasja; Muntingh, Anna D. T.; Evers, Aagje; van Straten, Annemieke; Sinnema, Henny; Spijker, Jan; Batelaan, Neeltje M.; van Meijel, Berno (Frontiers in Psychology, 2021)
Objective: To examine the underlying factor structure and psychometric properties of the Assessment of Self-management in Anxiety and Depression (ASAD) questionnaire, which was specifically designed for patients with (chronic) anxiety and depressive disorders. Moreover, this study assesses whether the number of items in the ASAD can be reduced without significantly reducing its precision. Methods: The ASAD questionnaire was completed by 171 participants across two samples: one sample comprised patients with residual anxiety or depressive symptoms, while the other consisted of patients who have been formally diagnosed with a chronic anxiety or depressive disorder. All participants had previously undergone treatment. Both exploratory (EFA) and confirmatory factor analyses (CFA) were conducted. Internal consistency and test-retest reliability were also assessed. Results: Both EFA and CFA indicated three solid factors: Seeking support, Daily life strategies and Taking ownership (Comparative Fit Index = 0.91, Tucker Lewis Index = 0.90, Root Mean Square Error of Approximation = 0.06 (CI 0.05-0.07), Standardized Root Mean Square Residual = 0.07 (χ2= 290.72, df = 176)). The ASAD was thus reduced from 45 items to 21 items, which resulted in the ASAD-Short Form (SF). All sub-scales had a high level of internal consistency (> α = .75) and test-retest reliability (ICC > .75). Discussion: The first statistical evaluation of the ASAD indicated a high level of internal consistency and test-retest reliability, and identified three distinctive factors. This could aid patients and professionals’ assessment of types of self-management used by the patient.